ANALISIS NILAI-NILAI KEHIDUPAN DALAM CERITA RAKYAT REJANG LEBONG - Ifnaldi, Ifnaldi; Wulandari, Tiara; Misriani, Agita (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2023)
This study aims to describe the values of life in the Rejang Lebong folklore, which is based on the community and the younger generation who do not know folklore in their own area so they do not know the values in it. This is due to the many media that attract more attention to be heard and seen, such as television, cell phones, social media; facebook, instagram, tiktok and so on. In fact, there are actually many benefits that can be drawn from various folklore that are still alive in society. Through folklore, we can find out the values of life that are very useful for the present because these values are related to each other in living life and can be instilled in us to become even better human beings. This type of descriptive research uses a content analysis approach. Data collection techniques used library research, data analysis techniques by reading, identifying, classifying, describing and presenting research results based on Haris Supratno's theory of life values. The results showed that the nine values contained in the Rejang Lebong folklore are in accordance with Haris Supratno's theory of life values, namely educational values, religious values, moral values, leadership values, heroism values, courage values, simplicity values, mutual cooperation values and sacrifice values. Keywords: The Value of Life, Rejang Lebong Folklore